Relating Wiener's cybernetics aspects and a situation awareness model implementation for information security risk management. Issue 1 (8th January 2018) - Anjaria, Kushal; Mishra, Arun
Abstract : Purpose: Situation awareness theory is a primary mean to take decisions and actions in a dynamically changing environment. Nowadays, to implement situation awareness, theories and models in organizational scenarios have become an important research challenge. The purpose of this paper is to investigate the relationship between the situation awareness theory and cybernetics. Further, the aim is to use this relationship to check the feasibility of situation awareness-based information security risk management (ISRM) implementation in the organizational scenario. Design/methodology/approach: To investigate the relationship between situation awareness theory and cybernetics, Endsley's situation awareness theory and Norbert Wiener's cybernetics concepts and philosophy have been used in the present work. For a detailed study, concepts, techniques and philosophy of the cybernetics have been extracted from the thesis of Norbert Wiener titled "The human use of human beings" and "Cybernetics or control and communication in the animal and the machine". Findings: The present paper demonstrates that relationship can be successfully established between cybernetics and situation awareness theory. Further, this relationship can be used to solve organizational implementation issues related to situation awareness based systems. To demonstrate relationship and solutions of implementation issues, two case studies related to ISRM are also incorporated in the present case study. Originality/value: The present work bridges two parallel and prominent theories of situation awareness and cybernetics. It also demonstrates that combination of both the theories can be used to feasibly implement situation awareness based systems in organizations.